A Fractal Description of Finely Ground Particles of Natural Quartz Using Particle Size and Image Analyses - Guzzo, Pedro L.; Ţălu, Ştefan; Kulesza, Slawomir; Bramowicz, Miroslaw (JOM (1989), 2023)
The morphological characteristics of mineral particles in ultrafine range have a significant influence on engineering processes but have not been extensively explored until now. In this study, the morphology of fine quartz particles produced in a planetary ball mill is considered using fractal geometry and stereometric tools in connection with particle size analysis. Structure functions and bidimensional shape factors were derived from numerical analysis of scanning electron micrographs using surface height functions and watershed algorithms. Secondary electron images were obtained from aliquots of clear and milky quartz samples ground up to 32 h. The fragmentation fractal dimension derived from the uniformity index of particle size distributions showed a distinct non-monotonical increase with the elapsed grinding time for each sample. Overall variations in fractal parameters (fractal dimension and corner frequency) and Feret’s diameter showed that the slowdown in particle size reduction and the onset of interparticle agglomeration occurred earlier for clear (monocrystalline) than for milky (polycrystalline) quartz. The onset of round-like agglomerates was also noticed with circular and round patterns. The loss of energy efficiency due to prolonged grinding processes was characterized by the decrease observed in the morphological fractal dimension.